463 PHYSICAL INTERACTION BETWEEN INSULIN-LIKE GROWTH FACTOR BINDING PROTEIN 3 AND ADIPONECTIN: IMPLICATIONS FOR INSULIN SENSITIVITY. (1st January 2006) - Joshi, A.; Yan, X.; Cobb, L.; Cohen, P.; Lee, K. -W.
Abstract : Background: Obesity is a disease that has reached epidemic proportions; approximately one-third of the adult population in the US is obese. Obesity is a complex multifactorial, chronic disease that is often associated with the prevalence of insulin resistance and type 2 diabetes. Investigation into the mechanism of these diseases may elucidate a method for controlling diabetes. Insulin-like growth factor binding protein 3 (IGFBP-3) is the principal carrier of insulin-like growth factor (IGF) in serum and is found in most tissue types. Besides modulating IGF actions, IGFBP-3 also has IGF-independent roles. Type 1 alpha collagen is one of the recently identified binding partners of IGFBP-3. Furthermore a recent study suggests that chronic infusion of IGFBP-3 into rodents may induce insulin sensitivity. Adiponectin, an adipocytokine, is another factor that may be involved in insulin sensitivity and contains a collagenous domain. Purpose of Study: We hypothesized that IGFBP-3 and adiponectin may physically interact. Methods Used: In order to study this interaction, in vitro and in vivo studies were conducted using co-immunoprecipitation, radioligand, and dot blot techniques. Summary of Results: Results from the in vitro studies using radiolabeled IGFBP-3 and co-immunoprecipitation in serum showed that IGFBP-3 and adiponectin may directly interact. The results from in vivo studies using co-immunoprecipitation of IGFBP-3 and adiponectin in adipocytes showed similar interaction and provide a correlate to the in vitro data. Conclusion: We propose that the interface between IGFBP-3 and adiponectin may provide a basis for molecular investigation of obesity in rodent models and humans. This may involve interaction and prevention of adiponectin's insulin-sensitizing effect. Further study may lead to therapeutics in the treatment of obesity and type 2 diabetes.